Mayonesas con contenido proteico mejorado y conservantes alimentarios naturales - Colombo Soares, Tiago (2024)
The aim was to prepare mayonnaises with natural preservatives and improved protein content to verify their structural and nutritional properties. Three formulations were developed (70% fat + variation in protein), F1 (powdered whey) did not reach the structural standards of commercial mayonnaise; F2 (skimmed milk) reached standards equivalent to commercialized products; F3 (powdered whey + skimmed milk) presented light mayonnaise pattern; F0 (Control). Protein content was higher than market products (more than 1.0 %). The evaluation of 30 days showed variations:  AW (0.934-0.941); extrusion values F1 (1.035 N ±0.026 – 0.566 N ±0.024), F2(4.255 N ±0.160 – 3.218 N ±0.060), F3 (3.198 N ±0.086 – 1.700 N ±0.044). The preservatives favored the color ∆E: F1 (11.31 ±0.04), F2 (2.65 ±0.14), F3 (1.65 ± 0.22). DPPH analysis showed the difference of products with added natural preservatives and whey in relation to the F0; F3 formulation was favored. Thixotropy appeared in all samples. The exothermic peak occurred F1 (6˚C - 7˚C), F2 (5˚C - 7˚C) and F3 (3˚C - 4˚C), indicating faster crystallization of the F3 (lipid-protein bond). The use of whey and powdered milk as emulsifying agent for mayonnaise emulsions, garlic and mustard, increased shelf life and protein content were demonstrated.